BONE COMPOSITION AND THE BIRTH OF QUANTITATIVE CHEMISTRY - De Santo, Natale Gaspare; De Santo, Rosa Maria; Pišot, Rado; Bisaccia, Carmela; Perna, Alessandra; Bizzarri, Mariano; Di Leo, Vito Andrea; Bilancio, Giancarlo; Cirillo, Massimo (Annales Kinesiologiae, 2011)
Bone is an important tissue for space specialists since it undergoes significant changes under microgravity conditions and its healing is slow. Bone has been considered a special tissue since the very inception of medical theories. In Akragas, Empedocles’ (493-432 BC) hypothesis regarding bone was that it was made of two parts earth, two parts water and four parts fire, thus marking the beginning of quantitative chemistry.